Traffic Sign Classification Using Deep Learning - Sicha, Marek (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
The thesis focuses on the classification of traffic signs in images and video sequences.The goal is real-time processing and usage of software in the vehicle. Neural networks and thePython programming language were chosen to solve the problem. To solve the problem a machinelearning method was chosen, more precisely a convolutional neural network. A neural network inthe Python programming language was created for the classification of traffic signs, using the Kerasand Tensorflow libraries. The neural network architecture is chosen for optimization for use on asingle-board computer with limited performance.
Keywords: classification; neural networks; traffic signs